The poetics of imitation in the Italian theatre of the Renaissance - Di Maria, Salvatore (Toronto Italian studies., 2013)
"The theatre of the Italian Renaissance was directly inspired by the classical stage of Greece and Rome, and many have argued that the former imitated the latter without developing a new theatre tradition. In this book, Salvatore DiMaria investigates aspects of innovation that made Italian Renaissance stage a modern, original theatre in its own right. He provides important evidence for creative imitation at work by comparing sources and imitations - incuding Machiavelli's Mandragola and Clizia, Cecchi's Assiuolo, Groto's Emilia, and Dolce's Marianna - and highlighting source elements that these playwrights chose to adopt, modify, or omit entirely